Clinically meaningful parameters of progression and long-term outcome of Parkinson disease: An international consensus statement. Issue 7 (July 2015) - Puschmann, Andreas; Brighina, Laura; Markopoulou, Katerina; Aasly, Jan; Chung, Sun Ju; Frigerio, Roberta; Hadjigeorgiou, Georgios; Kõks, Sulev; Krüger, Rejko; Siuda, Joanna; Wider, Christian; Zesiewicz, Theresa A.; et al.
Abstract Parkinson disease (PD) is associated with a clinical course of variable duration, severity, and a combination of motor and non-motor features. Recent PD research has focused primarily on etiology rather than clinical progression and long-term outcomes. For the PD patient, caregivers, and clinicians, information on expected clinical progression and long-term outcomes is of great importance. Today, it remains largely unknown what factors influence long-term clinical progression and outcomes in PD; recent data indicate that the factors that increase the risk to develop PD differ, at least partly, from those that accelerate clinical progression and lead to worse outcomes. Prospective studies will be required to identify factors that influence progression and outcome. We suggest that data for such studies is collected during routine office visits in order to guarantee high external validity of such research. We report here the results of a consensus meeting of international movement disorder experts from the Genetic Epidemiology of Parkinson's Disease (GEO-PD) consortium, who convened to define which long-term outcomes are of interest to patients, caregivers and clinicians, and what is presently known about environmental or genetic factors influencing clinical progression or long-term outcomes in PD. We propose a panel of rating scales that collects a significant amount of phenotypic information, can be performed in the routine office visit and allows international standardization. Research into the progression and long-term outcomes of PD aims at providing individual prognostic information early, adapting treatment choices, and taking specific measures to provide care optimized to the individual patient's needs.